47. CHANGE IN CARE KNOWLEDGE OF MOTHER WHOSE CHILDREN UNDER 5 YEARS OLD HAVE PNEUMONIA AT NATIONAL LUNG HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: Assessing the change in knowledge of mothers about caring for children under 5 years old with pneumonia at the Pediatric Department, National Lung Hospital in 2022 after health education intervention.Method: A health education intervention study with comparison before and after on 60 mothers with children under 5 years old with pneumonia treated at the Pediatric Department, National Lung Hospital from January to April. 2022.Results: Before the intervention, the percentage of mothers with correct knowledge about pneumonia was 58.1%. After health education, the percentage of mothers with correct knowledge about pneumonia was 100%. The difference was statistically significant with p
Keywords: Mother’s knowledge, pneumonia, chidren under 5 years old.